Bacterial auto-nemesis: templating polymers for cell sequestration - Magennis, Eugene Peter (2013)
The detection and control of microorganisms such as bacteria is important in a wide range of industries and clinical settings. Detection, binding and removal of such pathogenic contaminants can be achieved through judicious consideration of the targets which are available at or in the bacterial cell. Polymers have the ability to present a number of binding ligands for cell targeting on one macromolecule and so avidity of interaction can be greatly increased.